The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/sla.0b013e3182197035
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Different Bariatric Surgeries in the Treatment of Obesity and Insulin Resistance in Mice

Abstract: Objective To assess the effects of different bariatric surgical procedures on the treatment of obesity and insulin resistance in high fat diet-induced obese (DIO) mice. Background Bariatric surgery is currently considered the most effective treatment for morbid obesity and its comorbidities; however, a systematic study of their mechanisms is still lacking. Methods We developed bariatric surgery models, including gastric banding, sleeve gastrectomy, Roux-en-Y gastric bypass (RYGB), modified RYGB (mRYGB) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 47 publications
8
47
0
Order By: Relevance
“…In our work, circulating insulin was significantly increased in DIO mice, but it was reduced by BD, which is consistent with our previous finding that the RYGB procedure improves ␤-cell viability (61). Leptin, secreted by adipocytes, is linked to obesity, insulin resistance, and inflammatory responses.…”
Section: Discussionsupporting
confidence: 92%
“…In our work, circulating insulin was significantly increased in DIO mice, but it was reduced by BD, which is consistent with our previous finding that the RYGB procedure improves ␤-cell viability (61). Leptin, secreted by adipocytes, is linked to obesity, insulin resistance, and inflammatory responses.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, glucose tolerance in OAGB mice improved significantly and was comparable to that at the baseline evaluation. These results match experiences from other murine models of bariatric surgery [15, 19]. Chambers et al [20] observed similar effects on glucose tolerance in a mouse model of RYGB and sleeve gastrectomy.…”
Section: Discussionsupporting
confidence: 82%
“…Weight loss was rapid during the first week and continued moderately. Other authors observed similar effects on body weight after RYGB [15, 16]. Sustained weight loss after RYGB depends on the experimental diet and preoperative weight and ranges between 20 and 30% in the literature [16, 17].…”
Section: Discussionmentioning
confidence: 73%
“…During the experiment, 1 rat from the sham group, 1 rat from the RYGBP group and 2 rats from the RYGBP+IL group succumbed. This is in line with the mortality rates of rats in previous studies (25)(26)(27).…”
Section: Animalssupporting
confidence: 92%